1995
DOI: 10.1144/gsl.sp.1995.088.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Transpressional inversion due to episodic rotation of extensional stresses in Jeanne d’Arc Basin, offshore Newfoundland

Abstract: Variations in structural architecture indicate that a ninety degree rotation of extensional stresses occurred between multiple Mesozoic rift phases, resulting in local structural inversion in the Jeanne d'Arc Basin on the Grand Banks of Newfoundland, offshore eastern Canada.NW-SE-orientated extension caused dip-slip movement on NE-SW-trending en echelon faults during the Late Triassic to earliest Jurassic rift episode. These en echelon faults appear to have been separated by tilted basement relay ramps in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Only two of these mechanisms can generally cause shortening of rift basins (i.e., basin-scale compressive field), which are horizontal plate movement and strike-slip tectonics. Two mechanisms have been proposed to explain the transient-inversion episodes mentioned in the "Introduction" section of this work in different geological provinces of the world: first, ridge-push in the early stages of the oceanization of the eastern United States (Withjack et al 1998) and in the Red Sea (Arthaud and Choukroune 1976;Knott et al 1995), and second, transpression induced by rotation of the extension direction during rifting in the North Sea (Fossen 1989;Sinclair 1995;Thomas and Coward 1995).…”
Section: What Mechanism Originated the Early Transientmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two of these mechanisms can generally cause shortening of rift basins (i.e., basin-scale compressive field), which are horizontal plate movement and strike-slip tectonics. Two mechanisms have been proposed to explain the transient-inversion episodes mentioned in the "Introduction" section of this work in different geological provinces of the world: first, ridge-push in the early stages of the oceanization of the eastern United States (Withjack et al 1998) and in the Red Sea (Arthaud and Choukroune 1976;Knott et al 1995), and second, transpression induced by rotation of the extension direction during rifting in the North Sea (Fossen 1989;Sinclair 1995;Thomas and Coward 1995).…”
Section: What Mechanism Originated the Early Transientmentioning
confidence: 99%
“…Withjack et al (1995Withjack et al ( , 1998 described compressive structures formed during the rift-drift transition offshore the eastern United States and maritime Canada in the Early Jurassic-Early Cretaceous time interval. Fossen (1989), Sinclair (1995), and Thomas and Coward (1995) reported uplift associated with structural inversion in the North Atlantic during the Late Jurassic-Early Cretaceous transition. According to these authors, inversion resulted from oblique slip caused by rotation of the extension direction from NW-SE, which lasted from Late Triassic to Late Jurassic, to NE-SW in the Early Cretaceous.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of basin inversion has been documented worldwide. For example, mild to moderate inversion in intraplate basins has been observed in numerous North Atlantic basins (Cartwright, 1989;Chapman, 1989;Hayward & Graham, 1989;Roberts et al, 1993;Sinclair, 1995;Thomas & Coward, 1995) or in the North German Basin (Kossow et al, 2000;Kossow & Krawczyk, 2002;Gemmer et al, 2003). In addition, strongly shortened half grabens have been documented in the Alps (Gillcrist et al, 1987), with prominent examples found in the Central Andes (Kley & Monaldi, 2002) and Atlas mountains (Beauchamp et al, 1999;Teixell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although inversion tectonics have been mainly studied in extensional and compressional fault systems using models (Bally, 1984;Williams et al, 1989) and field examples (Gillcrist et al, 1987;Kelly et al, 1999), research into oblique-slip structures (e.g. Casas-Sainz, 1993;Sinclair, 1995;Thomas and Coward, 1995;Quintana et al, 2004) is more scarce. The inversion and reactivation of transfer faults have been studied in sedimentary basins mainly on the basis of geophysical data (e.g.…”
Section: Introductionmentioning
confidence: 99%